2004
DOI: 10.1088/0960-1317/14/7/007
|View full text |Cite
|
Sign up to set email alerts
|

Strong, high-yield and low-temperature thermocompression silicon wafer-level bonding with gold

Abstract: A systematic variation of process parameters for wafer-level thermocompression bonding with gold is presented for the first time. The process was optimized for high bond strength and high bond yield. In addition, the impact of the process temperature was investigated. A bond strength of 10.7 ± 4.5 MPa and a bond yield of 89% was achieved when bonding a wafer pair at 298 °C applying 4 MPa pressure for 45 min. A total of ten wafer pairs were bonded in a custom-built bonding tool and tested to establish the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 11 publications
4
41
3
Order By: Relevance
“…However, the applied bonding pressures used in the current study are probably lower than the pressures used by Tsau et al [17] and higher than the pressure used by Taklo et al [19]. The average bond strengths obtained on our three laminates were higher than the ~10 MPa reported by Taklo et al [19] and the ~ 20 MPa reported by Kurotaki et al [16]. Mean fracture loads of 20 MPa have been reported for glass frit bonds [3], indicating that 20 MPa can be a sufficient bond strength for device seals in industrial products.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, the applied bonding pressures used in the current study are probably lower than the pressures used by Tsau et al [17] and higher than the pressure used by Taklo et al [19]. The average bond strengths obtained on our three laminates were higher than the ~10 MPa reported by Taklo et al [19] and the ~ 20 MPa reported by Kurotaki et al [16]. Mean fracture loads of 20 MPa have been reported for glass frit bonds [3], indicating that 20 MPa can be a sufficient bond strength for device seals in industrial products.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in order to activate a getter material during the bonding process, a bonding temperature of 400 -450 °C can be demanded [18]. According to Park et al and Taklo et al, increased bonding temperature improves the bond quality [10,19], while Kurotaki et al did not find any relationship between bonding temperature and bond strength [16]. Several authors report that an increased bonding pressure increases bond quality [10,17,19], while the bonding time has been found to be of low importance for the final bond strength [10,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decades, many bonding schemes have been developed [7,[71][72][73][74][75][76][77][78][79][80][81][82][83][84], according to their bonding mechanisms, these processes can be classified as direct bonding, anodic bonding, and bonding with intermediate layer.…”
Section: Wafer Bonding and Device Packagingmentioning
confidence: 99%
“…To protect the bonding tool from damaging, the bonder must be cleaned periodically. On the other hand, during bonding, the ions may also diffuse into the counter wafer, i.e., they will bring contamination to the silicon substrate [84]. To avoid this effect, an additional barrier layer (e.g.…”
Section: Wafer Bonding and Device Packagingmentioning
confidence: 99%